Formation of Ag nanowires on graphite stepped surfaces: A DFT study - Ambrusi, Rubén Eduardo (2015)
We investigate the feasibility of obtaining silver nanowires on graphite stepped surfaces theoretically, using density functional theory calculations. Three layer slabs are used to model graphite surfaces with and without defects. Adsorption energies for Ag atoms on graphite surfaces were calculated showing the preference of Ag adatoms to locate on the steps, forming linear structures like nanowires. An analysis of the charge densities and projected densities of states for different structures is also performed.